Rhizosphere dynamics in contaminated soils: Unravelling plant, metal and microbe relationships - Suparna, K; Bharani , A; Kalaiselvi , T; Dhevagi , P; Malathi, P (Plant Science Today, 2025)
Heavy metal contamination from both natural and anthropogenic sources poses a significant environmental challenge, impacting human and animal health, as well as microbial populations. Microbes exposed to elevated metal concentrations develop resistance mechanisms, involving both physiological and genetic adaptations, to detoxify and transform metals. Recent advancements have elucidated the roles of metal-metabolizing bacteria and transport proteins during metal detoxification. Microbial inoculation with phytoremediation is termed as rhizoremediation, which enhances degradation of toxic compounds in soil, offering a promising solution to contamination issues. The synergistic relations between plants and microbes in the rhizosphere highlight the importance of root exudates in mediating microbial communities for plant nutrition and metal biotransformation. It is for these reasons that it is imperative to better understand these interactions in order to design more effective convention for the detoxification of metals for enhanced soil quality. The potential application of plant-microbe synergism in the remediation of metal pollutants using environmentally friendly and economically viable methods in soil remain scarce.